Improving Exposition Writing Skills through Online-Based Cycle Learning Models - Efendi, Roy; Sarimanah, Eri; Indra Dewi, Figiati; Syarifuddin (International Journal of Psychosocial Rehabilitation, 2020)
Exposition writing skills are one of the courses taught to Indonesian Language Education students. This writing exposition trains students to be more sensitive toward developed issues in society. Through identifying, recording, and collecting evidence or facts, exposition writing fits the topic using online media. Besides, writing expositions trains students to think critically, systematically, and emphasize structured thinking. Writing with a cycle learning model trains students' sensitivity to be able to generate interest, explore, explain, elaborate, and evaluate exposition writing. This study found that the online-based cycle learning model can improve student writing exposition skills.